Genetic Parameters of Birth Weight, Litter Size in Crossbreeding of Boer and Indonesian Goat - Rosidi Azis; Gatot Ciptadi; Suyadi Suyadi (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The study was conducted to analyze the genetic crossbreed of Boer and PE goats through the productivity of offspring by crossing based on birth weight and litter size. The material used is 65 goats from the Boer and PE goats consisting of males and females. Data analysis was estimated by calculating the probability of birth weight, litter size using the average and standard deviation based on Noor (1996) formula, then this data was analyzed using the t-test based on Steel and Torrie, (1991) to find out its significance. The results of crossing Boer and PE goats have a high productivity and proliferation rate with an average birth weight parity of male goats parity higher than female goats were 3,92±0,59 dan 3,87±0,90 (P<0,05). The results of the sex ratio of female goats were on average higher than males were 45.73% and 54.27%, respectively. The sex ratio of males is higher than females only in the third parity (64.29% and 35.71%).  The average yield of litter size of mothers who gave birth single, twins, and triplets (25%, 50%, and 25%). The results generally indicate that the litter size of the mother goat gave birth to twins and triplets by 80% and only 20% single. The highest litter size was at the fourth parity and the second parity (2.14 ± 0.11 and 1.86 ± 0.07 tails). The crossing of Boer and PE goats in the fourth parity has a high prolific rate. Goats with a fourth parity that are born with twin birth types and high birth weight can potentially have good genetic and could be used as stock prospective livestock in the future. Analysis of genetic parameters based on birth weight and litter size in goat to be a basis for selection could be achieved.